How are you doing today? Air quality and subjective well-being across time and space in Germany - Almut Balleer; Michael Hirsch; Marvin Nöller (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
We present evidence that air pollution negatively affects current well-being. To do so, we create a new dataset, matching particulate matter concentration at the exact day and location with individual-level survey responses about current life satisfaction. The panel structure of our data allows us to overcome several identification challenges in the literature. Additionally, we show how aggregation of air pollution across time and space mis-measures the relevant exposure. Our results further suggest that air pollution affects current well-being mostly through negative emotions like sadness or worry. We estimate the willingness to pay for clean air that refers to the direct, immediate effects of air pollution and can be mapped well to economic models. – – Luftverschmutzung beeinflusst das aktuelle Wohlbefinden negativ. Wir zeigen dies anhand eines neuen Datensatzes, in dem wir die Feinstaubkonzentration an einem bestimmten Tag und Ort mit individuellen Umfrageantworten zur aktuellen Lebenszufriedenheit abgleichen. Dank der Panelstruktur unserer Daten können wir hierbei mehrere Identifikationsprobleme aus der Literatur überwinden. Wir zeigen zudem, wie die Aggregation von Luftverschmutzung über Zeit und Raum zu einer falschen Messung der relevanten Belastung führt. Unsere Ergebnisse deuten darauf hin, dass Luftverschmutzung das aktuelle Wohlbefinden vor allem durch negative Emotionen wie Traurigkeit oder Sorgen beeinflusst. Darüber hinaus schätzen wir die kurzfristige Zahlungsbereitschaft für saubere Luft, die gut in ökonomische Modelle überführt werden kann.
Keywords: H41; I31; Q53; 330; Subjective well-being; air pollution; willingness to pay; compensating variation